Mitochondrial cytopathies and cardiovascular disease. Issue 8 (21st January 2014) - Dominic, Elizabeth A; Ramezani, Ali; Anker, Stefan D; Verma, Mukesh; Mehta, Nehal; Rao, Madhumathi
Abstract : The global epidemic of cardiovascular disease remains the leading cause of death in the USA and across the world. Functional and structural integrity of mitochondria are essential for the physiological function of the cardiovascular system. The metabolic adaptation observed in normal heart is lost in the failing myocardium, which becomes progressively energy depleted leading to impaired myocardial contraction and relaxation. Uncoupling of electron transfer from ATP synthesis leads to excess generation of reactive species, leading to widespread cellular injury and cardiovascular disease. Accumulation of mitochondrial DNA mutation has been linked to ischaemic heart disease, cardiomyopathy and atherosclerotic vascular disease. Mitochondria are known to regulate apoptotic and autophagic pathways that have been shown to play an important role in the development of cardiomyopathy and atherosclerosis. A number of pharmacological and non-pharmacological treatment options have been explored in the management of mitochondrial diseases with variable success.